Debondable adhesives and their use in recycling. Issue 1 (7th December 2021) - Mulcahy, Kira R.; Kilpatrick, Alexander F. R.; Harper, Gavin D. J.; Walton, Allan; Abbott, Andrew P.
Abstract : Structural adhesives are commonly used to join dissimilar materials and are of particular interest in complex technological devices but their use makes recycling difficult. Abstract : Structural adhesives are commonly used to join dissimilar materials and are of particular interest in complex technological devices used in automotive, telecommunications, photonic devices, aerospace and sustainable power production and storage. Their strength, ease of application and stability are of significant help in the manufacture and service of the device, however, they can present significant issues at end of life, particularly when technology critical metals need to be recovered. In this paper, we highlight some of the issues, and discuss an alternative approach: the use of adhesives that can be debonded upon application of an external stimulus. The aim of this critical review is to consider the polymer systems which have been investigated and suggest some alternative strategies. It also aims to demonstrate the different stimuli that can be used to debond and comment on the applicability of these with a number of case studies. Finally, the service conditions and process economics are considered together with a discussion of the Green benefits of this type of methodology.